The Concept of “Date of Issuing of the Judgment” Determining the Beginning of the Legal Period for Submitting an Application for Care Benefits for the Retrospected Period (Article 24(2a) of the Family Benefits Act) - Lewicka, Renata (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The subject of the considerations was the analysis of discrepancies in the interpretation of the starting date of the substantive legal term for submitting an application for a care benefit in the jurisprudence of administrative courts for the period from the date of submission of the application to the determination of disability or its degree.